EFFECT OF EMPLOYEE ENGAGEMENT AND WORKPLACE SPIRITUALITY OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR EMPLOYEES SUPERMARKETS AAA - Rizal Nopriyanto; Fatwa Tentama; Erita Yuliasesti Diah Sari (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
This study aims to examine the effect of employee engagement and workplace spirituality on organizational citizen behavior among AAA self-service employees. The sample used in this study were 60 employees from 100 AAA self-service employee populations. The sampling technique used in this study was purposive sampling technique. The instrument used was the employee engagement scale, workplace spirituality scale, and organizational citizenship behavior scale. The data analysis technique used is multiple linear regression analysis. The results of data analysis showed F = 176.195 with a value of p = 0.000 (p <0.01) which indicated that there was a very significant influence between employee engagement and workplace spirituality variables on organizational citizenship behavior of AAA self-service employees. The results of the subsequent analysis obtained a beta value of 0.464 with a significance level of 0.000 (p <0.01) indicating that there was a very significant positive effect between employee engagement on organizational citizenship behavior. The results of further analysis obtained a beta value of 0.500 with a significance level of 0.000 (p <0.01) indicating that there was a very significant positive effect between workplace spirituality on organizational citizenship behavior. Based on the results of research and discussion, it can be seen that employee engagement and workplace spirituality greatly affect organizational citizenship behavior of AAA self-service employees.